2019
DOI: 10.1515/bmc-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality of Life in Terms of Sinonasal Symptoms in Children with Cystic Fibrosis

Abstract: ObjectiveSinusitis is a common complaint in children with cystic fibrosis. However, the actual prevalence of chronic rhinosinusitis and its effect on the quality of life of children have not been well considered. Therefore, the objective of this study was to determine the effect of sinonasal quality of life in children with cystic fibrosis.Materials and methodsThis study was a diagnostic study performed on 80 children with cystic fibrosis ranging from 2 to 20 years old, who were referred to the cystic fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
3
2
2
Order By: Relevance
“…We found that females had higher RSDI and SNOT-22 scores and thus poorer QoL, which is consistent with a Vietnamese study proving CRS females have poorer QoL than men [ 30 ]. In our study only 10% of students were active smokers, which is less than the 25% reported in other studies [ 31 ]. One explanation for this difference is that the majority of respondents in our study were females, who traditionally do not smoke in our society [ 31 ].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…We found that females had higher RSDI and SNOT-22 scores and thus poorer QoL, which is consistent with a Vietnamese study proving CRS females have poorer QoL than men [ 30 ]. In our study only 10% of students were active smokers, which is less than the 25% reported in other studies [ 31 ]. One explanation for this difference is that the majority of respondents in our study were females, who traditionally do not smoke in our society [ 31 ].…”
Section: Discussioncontrasting
confidence: 90%
“…In our study only 10% of students were active smokers, which is less than the 25% reported in other studies [ 31 ]. One explanation for this difference is that the majority of respondents in our study were females, who traditionally do not smoke in our society [ 31 ].…”
Section: Discussioncontrasting
confidence: 90%
“…The exact prevalence of PCRS in patients with underlying conditions such as CF, PCD, or immunodeficiency is unknown but may be higher than in healthy children. Depending on the diagnostic criteria used for PCRS, some studies estimate the incidence of PCRS in children with CF to be 11% to 38%, 38,2321 for children with PCD to be as high as 40%, 39 and for children with CVID to be as high as 36% 40 …”
Section: Pediatric Rhinosinusitismentioning
confidence: 99%
“…Furthermore, the prevalence in patients with underlying comorbidities may be higher than in healthy children. Several studies estimate the presence of CRS in children with CF, primary ciliary dyskinesia (PCD), and common variable immunodeficiency to be 11% to 38%, 38 40%, 39 and 36%; 40 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Rhinosinusitis-related quality of life was evaluated using sinonasal outcome test 20 (SNOT-20) (30) . However, due to lack of validation of SNOT-20 in children, future studies should also incorporate other methods of QOL assessment including Sino-Nasal 5 (SN-5) questionnaire (31) .…”
Section: Quality Of Life Assessmentmentioning
confidence: 99%